TUTUR JATISWARA: ANALISIS BENTUK DAN FUNGSI - Maygayanti, Desak Komang; Darsana, I Nyoman; Suteja, I Wayan (Humanis; Volume 16. No. 2. Agustus 2016)
This analysis is discussed about Tutur Jatiswara text with its forms and functions analysis. This analysis is used to reveal structures that is developed literatures and its functions in it. Tutur Jatiswara study is using structural theory from Teeuw, and then functions theory from Damono and Ratna. Therefore, analysis about Tutur Jatiswara could be understood well. Technique and method that is used in this analysis is divided into three steps, they are (1) technique and method of data provision that used is reading method and be helped with take a note and translation method, (2) technique and method that is used to analysis data is qualitative methode, descriptive analytic technique, (3) technique and methode of result provision from data analysis that used is informal methode and be helped by deductive-inductive technique. The result obtained from this study is forms structure, they are: language manner and genre. Content structures are: introduction, middle, and final parts. Besides, this study also reveal functions that is contained in Tutur Jatiswara are, etnics (susila), philosophy (tattwa), yadnya, and self control functions.
Keywords: speech, form and function